The impact of accounting disclosure on new investors and the competitive environment on tourism companies in Jordan - Harb, Ayman Saleh Mustafa (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to identify the impact of accounting disclosure to new investors and competitive environment in the tourist companies in Jordan, by selecting the effect of accounting disclosure to new investors in the tourism companies in Jordan, and to determine the effect of accounting disclosure on the competitive environment in the tourism companies in Jordan. To achieve these goals, the researcher designed a questionnaire consisting of (18) items were distributed to the population of the study consists of tour operators in Jordan, and their number (8) Travel and Tourism companies by the end of 2015, noting that the study where there is no option for a sample of the community, set it study included all members of society, and represented the unit of analysis to individuals working in the accounting departments (financial, accountants, managers), circles and other sections in the tourism and travel industry with the end of 2015, with the distribution of (90) to identify the individuals working in these departments and sections , and the number of questionnaires filled is reached (12) questionnaire. This study has concluded that there is a statistically significant effect (first hypothesis) to the effect of accounting disclosure to new investors in the tourism companies in Jordan, where he reached the relationship between two variables value (0.738), and considers this value is statistically significant, because the value of (f ) calculated the (104.12) have a statistically significant level of significance (0.000), which is less than (5%), and indicate this result to the impact of accounting disclosure to new investors in the tourism companies in Jordan. As well as the study concluded that there is a statistically significant effect (for the second hypothesis) to the effect of accounting disclosure on the competitive environment in the tourism companies in Jordan, where he reached the relationship between two variables value (0.765), and considers this value is statistically significant, because the value of (f ) calculated the (122.59) have a statistically significant level of significance (0.001), which is less than (5%), and indicate this result to the impact of accounting disclosure on the competitive environment in the tourism companies in Jordan.
Keywords: accounting disclosure; new investors; competitive environment